Bedroom Crimes: When Private Desire Meets Criminal Law - Hamonangan Parsaulian Sidauruk; Koswara; Imam Maskur; Muhammad Shidqi Baidlowi; Tajudeen Sanni (Journal of Human Rights, Culture and Legal System, 2026)
Pornography offenses continue to raise significant legal concerns because criminal law seeks to safeguard morality, privacy, and human dignity, while the current regulatory framework still allows personal possession or storage of pornographic material. This exception creates uncertainty in legal interpretation, weakens enforcement, and limits protection for victims, especially in cases involving hidden recordings, digital exploitation, and misuse of intimate images when offenders claim personal use. This study aims to examine whether the regulation of pornography for personal use reflects justice, to identify weaknesses in the current legal framework, and to formulate a fairer regulatory reconstruction. This study employs a socio legal research method that combines normative legal analysis with empirical assessment of social realities, law enforcement practices, and public responses. The study evaluates statutory provisions together with actual cases to measure the gap between legal norms and practical implementation. The findings show that the current regulation does not achieve justice because the personal use exception creates a loophole that allows harmful conduct to avoid criminal sanctions. The study identifies three weaknesses. First, the substance of the law contains ambiguity and multiple interpretations that weaken its objectives. Second, the legal structure remains fragmented and less responsive to digital crime. Third, legal culture reflects permissive attitudes that treat pornography as a private matter despite broader social harm. This study concludes that lawmakers should remove the personal use exception and establish clear rules that ensure dignity, morality, privacy, certainty, and justice.